2008
DOI: 10.1007/s00417-008-1002-5
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-alpha-associated presumed ocular sarcoidosis

Abstract: Uveitis can be a sign of sarcoidosis induced by interferon alpha. Further studies are required to support the observation that with early diagnosis the prognosis of uveitis seems to be good.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 42 publications
0
32
0
Order By: Relevance
“…Azathioprine, methotrexate, tacrolimus and mycophenolate mofetil are used but based mostly on experience rather than on evidence. Caution must be observed with biological agents, such as anti-TNF agents and interferon-alpha, as sarcoidosis has been reported to develop during treatment with these agents or rheumatic disease [24,25]. Etanercept may induce sarcoid intermediate uveitis [26].…”
Section: Therapeutic Strategymentioning
confidence: 99%
“…Azathioprine, methotrexate, tacrolimus and mycophenolate mofetil are used but based mostly on experience rather than on evidence. Caution must be observed with biological agents, such as anti-TNF agents and interferon-alpha, as sarcoidosis has been reported to develop during treatment with these agents or rheumatic disease [24,25]. Etanercept may induce sarcoid intermediate uveitis [26].…”
Section: Therapeutic Strategymentioning
confidence: 99%
“…One hypothesis that has garnered considerable attention involves the inverse and interdependent relationship between TNFα and interferon levels (both α and γ), and the role of increased interferon in the development of autoimmune diseases, 31 including both psoriasis 32 and sarcoidosis. 33,34 Similar changes in the cytokine balance in response to TNFα inhibition have been suggested to elicit auto-antibody and immune complex formation, both of which may have broadly inflammatory effects. 35 Others have suggested that TNFα inhibition may directly or indirectly increase the rate of infection by organisms implicated in noncaseating granuloma formation, such as Propionibacterium acnes and nontuberculous Mycobacterium species.…”
mentioning
confidence: 82%
“…53 Other medications can also result in either toxic demyelination or inflammation of the chiasm. Ethambutol has been shown to cause demyelination of the optic nerves, tracts, and chiasm, with the initial lesions showing a predilection for the optic chiasm in primates and rats.…”
Section: Medication Related and Mitochondrial Toxicitymentioning
confidence: 99%
“…Noncaseating granulomatous inflammation has been reported in various organ systems of patients undergoing therapy with interferon and ribavirin for hepatitis C. 53 One cases series demonstrated granulomatous panuveitis in 3 patients undergoing interferon-a therapy for hepatitis C. 53 There is also one case report of interferon and ribavirin therapy causing granulomatous adenohypophysitis in the setting of hepatitis C. 54 The association between these medications, particularly interferon-a, and a sarcoidosis-like disorder, has been reported to occur in several organ systems. 53 Other medications can also result in either toxic demyelination or inflammation of the chiasm.…”
Section: Medication Related and Mitochondrial Toxicitymentioning
confidence: 99%